2014
DOI: 10.1155/2014/685425
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Gland Involvement by Thyroid Cancer: Results from a Large Series of Thyroidectomies Performed in Two Italian University Hospitals and Review of the Literature

Abstract: Objectives.Parathyroid involvement by thyroid cancer (TC) has not been frequently investigated in thyroidectomy-based studies. We aimed to detect cases of parathyroid invasion by TC in a large series of thyroidectomies and to review the literature on this topic. Study Design. A 10-yr period database research was made from the files of the Section of Pathology of two Italian University Hospitals. Out of 22,310 thyroidectomies, 10 patients with parathyroid involvement by TC were found. Results. The 10 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition to primary malignancies of the parathyroid (parathyroid carcinoma), secondary (metastatic or infiltrating) malignant neoplasms from various organs can also deposit in the parathyroid glands (35). Very recently, Shifrin et al highlighted the importance of considering metastatic disease in the parathyroid glands as these are often overlooked and discovered incidentally at autopsy or during surgery for primary hyperparathyroidism (13,14,35,(108)(109)(110)(111)(112)(113)(114). For instance, direct extension from thyroid carcinomainto the parathyroid glands may occur in up to 4% of patients with thyroid carcinoma (35,108,110).…”
Section: Ancillary Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to primary malignancies of the parathyroid (parathyroid carcinoma), secondary (metastatic or infiltrating) malignant neoplasms from various organs can also deposit in the parathyroid glands (35). Very recently, Shifrin et al highlighted the importance of considering metastatic disease in the parathyroid glands as these are often overlooked and discovered incidentally at autopsy or during surgery for primary hyperparathyroidism (13,14,35,(108)(109)(110)(111)(112)(113)(114). For instance, direct extension from thyroid carcinomainto the parathyroid glands may occur in up to 4% of patients with thyroid carcinoma (35,108,110).…”
Section: Ancillary Biomarkersmentioning
confidence: 99%
“…Very recently, Shifrin et al highlighted the importance of considering metastatic disease in the parathyroid glands as these are often overlooked and discovered incidentally at autopsy or during surgery for primary hyperparathyroidism (13,14,35,(108)(109)(110)(111)(112)(113)(114). For instance, direct extension from thyroid carcinomainto the parathyroid glands may occur in up to 4% of patients with thyroid carcinoma (35,108,110). Most parathyroid glands are located within the thyroid pseudocapsule or within the thyroid gland, and intrathyroidal parathyroid carcinomas can mimic a variety of tumors including medullary thyroid carcinoma, thyroid paraganglioma, secondary (metastatic) neuroendocrine carcinoma and poorly differentiated thyroid carcinoma.…”
Section: Ancillary Biomarkersmentioning
confidence: 99%
“…Papi et al 6 found the most predominant form of spread was through direct invasion (6 of 10 cases). This is in keeping with our patient, seen in the pathological specimen ( Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 97%
“…Six different series describing this phenomenon have been published; 1 from Greece, 3 1 from Saudi Arabia, 4 1 from Italy 6 and 3 from Japan. 5 , 7 These studies suggest a predominance in women; however, it must be noted that the sample size is very small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation